Correlation Between Lipid Accumulation Product and Metabolic Dysfunction-Associated Steatotic Liver Disease in Chinese Adults with Type 2 Diabetes Mellitus - Liu W; Xu L; Yu Y; Qiao L; Zhang L; Chu X; Jing H; Cao L (Diabetes, Metabolic Syndrome and Obesity)
Wei Liu,1,* Lingling Xu,1,* Yuan Yu,2 Liang Qiao,1 Lijuan Zhang,1 Xiaoqiu Chu,1 Haibo Jing,3 Lin Cao1 1Department of Endocrinology, Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210028, People’s Republic of China; 2Department of Gastroenterology, Jiangning Hospital of Traditional Chinese Medicine, Nanjing, Jiangsu, 211100, People’s Republic of China; 3Department of General Surgery, Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210028, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Cao, Department of Endocrinology, Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing University of Chinese Medicine, NO. 100 Shizi Street, Hongshan Road, Nanjing, Jiangsu, 210028, People’s Republic of China, Tel/Fax +86-25-85608733, Email guodongcl@163.com Xiaoqiu Chu, Department of Endocrinology, Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing University of Chinese Medicine, NO. 100 Shizi Street, Hongshan Road, Nanjing, Jiangsu, 210028, People’s Republic of China, Tel/Fax +86-25-85608735, Email chumickey@126.comObjective: To evaluate the value and feasibility of the lipid accumulation product (LAP) in the prediction of metabolic dysfunction-associated steatotic liver disease (MASLD) in Chinese adults with type 2 diabetes mellitus (T2DM).Methods: In this cross-sectional study, we assessed the value of LAP and other novel indices in the prediction of MASLD in Chinese adults with T2DM in a total of 642 patients. Receiver Operating Characteristic (ROC) curves were plotted to assess the predictive ability of the indices for the occurrence of MASLD in T2DM.Results: The results showed that LAP had a strong predictive ability for the occurrence of MASLD in T2DM in both men and women and was superior to other traditional visceral fat-related indices. In men, the area under curve (AUC) (95% CI) was 0.815 (0.771– 0.859) with cut-off value of 36.01, and its sensitivity and specificity were 71.91% and 77.44%, respectively. And in women, the AUC (95% CI) was 0.816 (0.762– 0.870) with cut-off value of 24.22, and its sensitivity and specificity were 84.93% and 63.54%, respectively.Conclusion: LAP has a high predictive ability for the occurrence of MASLD in T2DM in both men and women and are superior to other traditional visceral fat-related indices.Keywords: diabetes mellitus, type 2, metabolic dysfunction-associated steatotic liver disease, lipid accumulation product